Silagens de ração total a base de capim-tanzânia e subprodutos da agroindústria do babaçu - BANDEIRA, Danrley Martins (2022)
The objective was to evaluate the quality of tanzania grass silages in the form of total ration with the inclusion of regional agroindustry by-products as a nutritional alternative for ruminants. Both experiments were carried out with the objective of evaluating the fermentative profile, to determine the chemical composition of total feed silages with babassu by-products, as a nutritional alternative for dairy cattle and sheep, respectively. A completely randomized design (DIC) was used, with four treatments and five replications, for both treatments were SCT: Tanzania grass silage (control); SRTP: Tanzania grass silage with corn and soybean meal (standard diet); SRTF: Tanzania grass silage with corn, soybean meal and babassu flour; SRTT: Tanzania grass silage with corn, soybean meal and babassu pie. However, the proportions of roughage and concentrate were different, 60:40 (cattle laying); 50:40 (sheep diet), in addition to variations related to formulations. There was a significant effect (P<0.05) for the variables, pH, ammoniacal nitrogen (N-NH³), gas losses (PG), effluent losses (PE), dry matter recovery (RMS) and soluble carbohydrates (CSA ). However, there was no statistical difference for buffer power (PT). The highest pH value was observed for the SRTT treatment, showing no difference between the SRTP and SRTF treatments, and the lowest value for SCT (P<0.0001) in the first trial, while for the second trial the lowest value was assigned to SRTP. There was no significant difference between treatments for the PT variable (P=0.3313). However, for the N NH3 variable, there was a significant difference (P<0.0001) in which the lowest values were observed in SRT silages, and the highest value for SCT. Higher (P<0.0001) PG and PE were found for SCT silage compared to SRT. SRT obtained higher RMS values in relation to SCT (P<0.0010). For CSA (P<0.0001) the highest values were for SRT silages in relation to SCT . For the chemical composition variables, higher values (P<0.0001) of MS, CP, and TDN were observed for the SRT treatments in relation to the SCT treatment. However, for the variables NDFcp and ADF, the highest values refer to the SCT treatment. The variables CT (P<0.0001) and CNF (P=0.0003) differed statistically between whether, the SRT silages presented lower values of total carbohydrates in relation to SCT. As for the CNF variable, the silages presented higher averages in relation to the SCT silage. The variables LIG, CEL, EE and aerobic stability (AE) did not show significant difference for both experimental tests. The by-products of babassu pie and starchy flour can be possible substitutes for 50% of corn in total diets containing tanzania grass silage, meeting the proposal of total ration silage. Proving to be equivalent in fermentation profile and bromatological composition to standard concentrates, in addition to reducing the costs of diets for dairy cows of medium production of beef sheep in confinement, depending on availability in the region.